Mindfulness-based interventions in schools—a systematic review and meta-analysis - Zenner, Charlotte; Herrnleben-Kurz, Solveig; Walach, Harald (Frontiers in Psychology, 2014)
Mindfulness programs for schools are popular. We systematically reviewed the evidence regarding the effects of school-based mindfulness interventions on psychological outcomes, using a comprehensive search strategy designed to locate both published and unpublished studies. Systematic searches in 12 databases were performed in August 2012. Further studies were identified via hand search and contact with experts. Two reviewers independently extracted the data, also selecting information about intervention programs (elements, structure etc.), feasibility, and acceptance. Twenty-four studies were identified, of which 13 were published. Nineteen studies used a controlled design. In total, 1,348 students were instructed in mindfulness, with 876 serving as controls, ranging from grade 1 to 12. Overall effect sizes were Hedge's g = 0.40 between groups and g = 0.41 within groups (p < 0.0001). Between group effect sizes for domains were: cognitive performance g = 0.80, stress g = 0.39, resilience g = 0.36, (all p < 0.05), emotional problems g = 0.19 third person ratings g = 0.25 (both n.s.). All in all, mindfulness-based interventions in children and youths hold promise, particularly in relation to improving cognitive performance and resilience to stress. However, the diversity of study samples, variety in implementation and exercises, and wide range of instruments used require a careful and differentiated examination of data. There is great heterogeneity, many studies are underpowered, and measuring effects of Mindfulness in this setting is challenging. The field is nascent and recommendations will be provided as to how interventions and research of these interventions may proceed.